2008
DOI: 10.1116/1.2870228
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of TiO2 thin films by laser ablation for photocatalytic applications

Abstract: Enhancement of optical absorption by modulation of the oxygen flow of TiO2 films deposited by reactive sputteringBandgap renormalization in titania modified nanostructured tungsten oxide thin films prepared by pulsed laser deposition technique for solar cell applications J. Appl. Phys.Thin titanium dioxide ͑TiO 2 ͒ films were deposited by pulsed KrF excimer laser ablation deposition system using a titanium oxide target. The effects of substrate temperature and oxygen partial pressure on the phase formations of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 28 publications
2
7
0
Order By: Relevance
“…The reported k values and those found herein are in agreement; however, the effect of anatase fraction on the k value was not shown in Ref. 23. Jung and Park 24) studied the decomposition of trichloroethylene using the photocatalytic activity of TiO 2 synthesized by the sol-gel method and reported that TiO 2 with an anatase fraction of 0.9 exhibited a superior decomposition rate than that with a single-phase anatase.…”
Section: Effect Of Nb Content On Photocatalytic Activitysupporting
confidence: 80%
See 1 more Smart Citation
“…The reported k values and those found herein are in agreement; however, the effect of anatase fraction on the k value was not shown in Ref. 23. Jung and Park 24) studied the decomposition of trichloroethylene using the photocatalytic activity of TiO 2 synthesized by the sol-gel method and reported that TiO 2 with an anatase fraction of 0.9 exhibited a superior decomposition rate than that with a single-phase anatase.…”
Section: Effect Of Nb Content On Photocatalytic Activitysupporting
confidence: 80%
“…In Fig. 8, the rate constants of MB decomposition on the anatase-type TiO 2 layer ( f A = 1), fabricated by the pulsed laser ablation method, 23) are shown for comparison, where the irradiation conditions, such as the UV light source irradiance of 1.6 mW·cm ¹2 and the initial MB concentration of 0.031 mM, Formation of Photocatalytically Active TiO 2 Layers on TiNb Alloys by Two-Step Thermal Oxidation were close to those used in this study. The reported k values and those found herein are in agreement; however, the effect of anatase fraction on the k value was not shown in Ref.…”
Section: Effect Of Nb Content On Photocatalytic Activitymentioning
confidence: 99%
“…Control of both crystal and aggregated structures are desired for catalytic applications. However the effects of background gas on the crystal structure and/or morphology of TiO 2 are described in many literatures, the correlation between structure and preparation conditions is discussed rather empirically [7][8][9][10][11][12]. The formation processes of atomic microstructure and aggregated nanocrystals have been clarified for PLA of silicon target in H 2 gas [6].…”
Section: Introductionmentioning
confidence: 98%
“…The transformation to rutile phase is irreversible, and the melting point of TiO 2 is 1858 • C [8,14,15]. Furthermore, the currently known methods to crystallize amorphous TiO 2 films into anatase or rutile phases require the annealing step, including oxygen plasma treatment [16][17][18]. Anatase crystals exhibit excellent optical properties, higher photocatalytic activity and gas sensing properties than rutile ones, and a lower electron-hole recombination rate.…”
Section: Introductionmentioning
confidence: 99%